Pure waterjet drilling of articular bone - Dunnen, Steven den (Strojniški vestnik, 2013)
The clinical application of waterjet technology for machining tough human tissues, such as articular bone, has advantages, as it produces clean sharp cuts without tissue heating. Additionally, water supply is possible via flexible tubing, which enables minimally invasive surgical access. This pilot study investigates whether drilling bony tissue with pure waterjets is feasible. Water pressures between 20 and 120 MPa with an orifice of 0.6 mm were used to create waterjets to drill blind borings in the talar articular surface of cadaveric calcaneus bones of humans, sheep, goats and pigs. A stand-off distance between 2.5 and 5.5 mm and a jet-time of 5 seconds were chosen. The depth of the holes was measured using a custom-adapted dial gauge. At least 30 MPa of water pressure is required to penetrate the human and goat specimens, and 50 MPa for the pig and sheep specimens. Overall, the machined holes were conically shaped and increased in depth with an increase of pressure. Above certain pressure levels, pure waterjets can be used for machining holes in articular bone, thereby opening a window for further research on pure waterjet drilling in orthopedics.
Keywords: čisti vodni curek; drilling articular bone; orthopedic treatment; ortopedska kirurgija; pure water jet; sklepni deli kosti pri sesalcih; vodni tlak; vrtanje z vodnim curkom; water jet drilling; water pressure